2017
DOI: 10.3390/rs9121317
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Tropospheric Delays Retrieved from Multi-GNSS Observations and IGS Real-Time Product Streams

Abstract: Abstract:The multi-constellation Global Navigation Satellite Systems (GNSS) offers promising potential for the retrieval of real-time (RT) atmospheric parameters to support time-critical meteorological applications, such as nowcasting or regional short-term forecasts. In this study, we processed GNSS data from the globally distributed Multi-GNSS Experiment (MGEX) network of about 30 ground stations by using the precise point positioning (PPP) technique for retrieving RT multi-GNSS tropospheric delays. RT satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…However, this is expected to be improved with new BDS satellites launched into orbit and a more densified tracking network in the near future [19,38]. In addition, although the RMS values of the along-track and cross-track components are larger than those of the radial component, the positioning users on the Earth's surface are less sensitive to errors in along-track and cross-track directions than to those in the radial direction; the orbit errors in the along-track and cross-track directions may therefore have a less significant impact on the accuracy of user positioning [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is expected to be improved with new BDS satellites launched into orbit and a more densified tracking network in the near future [19,38]. In addition, although the RMS values of the along-track and cross-track components are larger than those of the radial component, the positioning users on the Earth's surface are less sensitive to errors in along-track and cross-track directions than to those in the radial direction; the orbit errors in the along-track and cross-track directions may therefore have a less significant impact on the accuracy of user positioning [24].…”
Section: Discussionmentioning
confidence: 99%
“…2018, 10, 337 4 of 19 In order to transform the RAC corrections into ECEF corrections, the transformation matrix R has to be computed first; it is expressed as [18]: Following this, the ECEF orbit corrections δX t for epoch t can be derived by:…”
Section: Computation Methods Of Real-time Precise Satellite Orbits Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-GNSS observations have been intensively used to improve the precision of the tropospheric parameters retrieved from the PPP technique. Lu et al [11] evaluated the performance of the real-time ZTD estimated from single and multi-GNSS observations, and the results indicated that the precision and reliability of the troposphere estimates could be improved by using multi-GNSS data. Lu et al [12] further demonstrated that the initialization time and the precision of multi-GNSS tropospheric delays could be improved by using the PPP ambiguity-fixing technique, which can meet the requirements of the troposphere estimates for time-critical meteorological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Significant development has been achieved in the past few years [2][3][4][5][6][7][8]. In comparison with established atmospheric sounding techniques, GPS has extensive application prospects for sounding water vapor since it has the unique advantages of all-weather availability, high accuracy, long-term stability, and high time resolution [9,10].…”
Section: Introductionmentioning
confidence: 99%